40‐4: Development of Color Resists Containing Novel Dyes for Liquid Crystal Displays. Issue 1 (May 2016) - Tatsumi, Yasuki; Inoue, Masato
Abstract : To improve the color property of liquid crystal displays (LCDs) has been a subject of much interest. We have developed a new series of color photoresists (DyBright®) for LCDs which contains novel dyes and that improves the brightness of color filters.